Electro-mechanically controlled continuously variable transmission system for passenger cars - Mohiuddin, A. K. M.; Rahman, Mohammed Ataur (2009)
Electro-mechanically controlled continuously variable transmission (CVT) system is an automatic transmission system that can change the gear ratio to any arbitrary setting within the limits. This system includes an AC motor, set of power screw, an electromagnetic pick-up sensor, and two DC motors. Electromagnetic wheel speed sensor (WSS) generates the voltage with the travelling speed of the vehicle for operating the DC motor with a double acting magnetic pull-in solenoid switch. The function of power screw mechanism is for shifting movable sheaves axially along the shafts by the DC motor. Both the driving and driven pulleys’ moving sheave move at the same time exactly the same linear distance but in opposite directions. The relationship between the DC motor speed and its response time to actuate the moveable sheave was studied. The response time is the time needed for the sheave to travel axially covering all of its stroke length. The response time was derived from motor rpm and its linear speed provided that the whole stroke length equals to 13.6 mm.